Classification of global measles cases in 2013-17 as due to policy or vaccination failure: a retrospective review of global surveillance data - Minal K Patel, MD; Walter A Orenstein, ProfMD (Elsevier, 2019)
Summary: Background: Despite improvements in reported coverage of measles-containing vaccine (MCV) and progress towards elimination of measles, 172 939 measles cases were reported worldwide in 2017. Questions have been raised about whether measles cases are due to failure of immunisation programmes or vaccine policy failure, which might require changes to vaccination schedules or number of doses. Methods: This retrospective review of global surveillance data analysed case-based data for cases of measles occurring during 2013-17 submitted to WHO by its member states. Cases were classified as programmatically preventable (ie, did not receive the age-appropriate number of doses for that country) or programmatically non-preventable (ie, appropriately vaccinated as per national programme) on the basis of age at onset, year of birth, vaccination status, and eligibility for MCV doses in the country reporting the case. We grouped reasons why cases were non-preventable into four categories as follows: (1) received at least two doses of MCV; (2) too young for first dose; (3) received one dose but was too young to receive the second; or (4) was only eligible for one dose according to the national schedule. We analysed numbers and proportions of preventable and non-preventable cases of measles by region and year, reasons for non-preventable cases by year, preventable cases by age group, and preventable and non-preventable cases, including reasons for non-preventable cases, by measles elimination status of countries. Findings: Between Jan 1, 2013, and Dec 31, 2017, 634 139 measles cases were reported; 7850 (1%) cases were excluded because they did not provide age at onset, so 626 289 were included in our analysis. 191 333 (31%) of these cases had unknown vaccination status. 275 754 (63%) of the 434 956 cases with available vaccination data were categorised as programmatically preventable, 213 461 (77%) of whom were aged 1 year to less than 15 years. 156 384 (36%) cases were categorised as non-preventable, of whom 38 677 (25%) were two-dose vaccine recipients, 74 438 (48%) were too young to receive their first MCV dose, 11 914 (8%) received their first dose and were too young to receive their second dose, and 31 355 (20%), mostly in the Africa region, were non-preventable because they were only eligible for one dose on the basis of the national immunisation programme. Interpretation: Most measles cases during 2013-17 were programmatically preventable, highlighting the need for improving the effectiveness of immunisation programmes that already exist. Individual countries should do similar analyses to establish the changes needed in their country to decrease numbers of measles cases. Funding: None.